Studies on Dielectric relaxation and AC Conductivity of 3- Methoxy-4-(2-Hydroxy-3-Methacryloloxy-Propoxy) Benzaldehyde (MH) and Methacrylamide (MAA) Copolymers: Composition Dependence (International Journal of Innovative Research in Engineering & Management, 2023)
Systematic measurement of dielectric  constant (ε) and loss (tanδ) on powder pressed pellets of  MH and MAA copolymers in composition 10/90, 20/80, 50/50 have been carried out in the frequency range 200Hz 100kHz and in the temperature range from room  temperature to 180oC covering through the glass transition  temperature, Tg. Two sets of relaxation peaks one slightly  above room temperature and the other slightly above Tg are noticed from tanδ versus temperature curves for different  frequencies. The peaks are attributed to β- and α relaxations. Further the peaks shift towards higher  temperatures with increase of MH content in the  copolymer. The enhanced dielectric behavior is observed  in the case of MH-MAA (50/50). The results are discussed  in the light of increase in MH content in the copolymer.
Keywords: Dielectric constant (ε); Dielectric loss (tanδ); AC conductivity. Relaxation; segmental motion